Methodological Pluralism in Business and Information Systems Engineering? - Loos, Peter; Mettler, Tobias; Winter, Robert; Goeken, Matthias; Frank, Ulrich; Winter, Alfred (Business & information systems engineering, 2013)
For some time now, the Business and Information Systems Engineering (BISE) research community in the German-speaking countries has continuously been concerned with the development of the field as scientific discipline. This may be attributed to several reasons. First, it is a natural and necessary process for a scientific community to self-critically reflect its own discipline from time to time, especially after growth phases of a young science or after changes in the objects of research caused by technological innovations. Another reason is the necessity of internationalization, which among others led to a discussion of methods regarding behaviorist oriented and design science oriented research approaches in BISE (sterle et al. 2010). Following this, concerns have been expressed that design-oriented approaches commonly used in German-speaking countries will yield to more behavioral approaches in the future due to the pressure to publish internationally, which would not only lead to a loss of identity of German BISE but also to a reduction of the methodological pluralism harmful to the relevance of the discipline.